Modification of Areca Nut (Areca catechu L.) Peel Hydrochar for Photodegradation of Methylene Blue - Eva Musifa; Neza Rahayu Palapa; Titah Maharti Nugraheni; Miftahun Naimah (Chemistry Department, Mathematics and Natural Science Faculty, Tadulako University, 2025)
Synthetic dyes such as methylene blue (MB) are persistent pollutants that pose serious environmental risks due to their toxicity and resistance to biodegradation. This study investigates the development of sustainable photocatalysts derived from Areca catechu L. peel through hydrothermal carbonization, followed by activation, zeolite impregnation, and magnetic modification using Fe2+/Fe3+ ions. XRD and FTIR analyses confirmed the successful formation of Fe3O4, increased porosity, and the presence of functional groups that facilitate adsorption and photocatalytic activity. The results indicate that photodegradation is significantly more effective than adsorption, with magnetic hydrochar and hydrochar–zeolite composites achieving degradation efficiencies above 90%. Optimal performance was observed at a catalyst mass of 0.20 g and an irradiation time of 150 minutes. The high removal efficiency is attributed to synergistic interactions including pi-pi stacking, hydrogen bonding, and electrostatic attraction between MB molecules and the modified hydrochar surface. Overall, this study demonstrates that Areca catechu L. peel waste can be valorized into an efficient, low-cost, and magnetically recoverable photocatalyst for dye-contaminated wastewater treatment